THE EFFECT OF GROUP INVESTIGATION TYPE COOPERATIVE LEARNING MODEL ON STUDENTS’ LEARNING OUTCOMES ON THE THEMES OF DAERAH TEMPAT TINGGALKU AT GRADE IV SDN 094117 BANGUN SARIBU - Pitti Diana Girsang; Darinda Sofia Tanjung; Dewi Anzelina (JURNAL PAJAR (Pendidikan dan Pengajaran), 2021)
This research aimed to find out the effect of group investigation type cooperative learning model on the students’ learning outcomes. This was a non class action research utilizing descriptive analytic methods. The population of this research was all grade IV students at SD Negeri 094117 Bangun Saribu  consisting of 2 classes with a total of 57 students. The samples were chosen by using simple random sampling and 20 students were selected as the samples. The results of this research revealed that after implementing group investigation type cooperative learning model, the students’ learning outcomes were categorized as very good with an average of 80. The results of the correlation test obtained the result of 0.820 meaning that rcount  (0.820) > rtable (0.361); thus, ha was  accepted. After that, the results of t-test in which  tcount > ttable was 7.568 > 1.69. this implied that the hypothesis Ha was accepted. In other words, group investigation type cooperative learning model gave significant influence on students’ learning outcomes on the theme of “Daerah Tempat Tinggalku” at grade IV SD Negeri 094117 Bangun Saribu.